An Analysis of Denotative and Connotative Meaning in the Song "The Man Who Can't Be Moved" by The Script - Bhets Dewani Sipayung; Bernieke Anggita Ristia Damanik (JURNAL ILMIAH NUSANTARA, 2026)
. A fundamental area of linguistics that investigates the various ways meanings arise and operate is semantics, which is commonly described as the study of meaning in language. This study focuses on song lyrics, which use subtle expression to effectively communicate feelings, narratives, and concepts. In particular, it examines the lyrics of "The Man Who Can't Be Moved" by The Script, a moving song about unwavering love and perseverance, for both denotative (literal, dictionary-based) and connotative (implied, associative) meanings. The study uses a qualitative descriptive methodology based on Geoffrey Leech's groundbreaking semantics theory, which identifies seven meaning categories, including conceptual, connotative, and affective. This approach uses in-depth textual analysis to identify common linguistic devices found in the songs, such as inference and metaphor.Results show that denotative meanings (two occurrences) are less common than connotative meanings (three instances). The song's use of metaphorical language—such as symbolic waiting on a street corner—instead of direct narration to elicit emotional depth is reflected in connotative dominance, despite the narrow margin. This demonstrates how lyrics emphasize interpretive, evocative layers in order to connect with listeners.